Kontribusi Kepemimpinan Authentic, Kecerdasan Emosional, Efikasi Diri, dan Komitmen Organisasional Terhadap Kinerja Guru di SMP Negeri 2 Kuta Utara - H. Claranzia; A.A.G. Agung; I.M. Yudana (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aims to identify: (1) the contribution of authentic leadership towards teacher performance, (2) the contribution of emotional intelligence towards teacher performance, (3) the contribution of self-efficacy towards teacher performance, (4) the contribution of organizational commitment towards teacher performance, (5) the contribution of authentic leadership, emotional intelligence, self-efficacy, organizational commitment simultaneously towards the teacher performance at SMP Negeri 2 Kuta Utara. The population and samples of this study were 70 teachers. This study is classified as ex-post-facto with descriptive statistics analysis, simple correlation, partial correlation, multiple correlation, and multiple regression data analysis design. The data for this study were collected by using the Five-point Likert scale questionnaire model. The findings of this research revealed that (1) there is a positive and significant corellation between authentic leadership and teacher performance with 0,797 (ryx1) product moment coefficient correlation, 0,377 (ry.x1-x2,3,4) partial correlation coefficient, and 22,15% contribution of authentic leadership towards teacher performance, (2) There is a positive and significant correlation between emotional intelligence and teacher performance with 0,816 (ryx2) product moment coefficient correlation, 0,312 (ry.x2-x1,3,4) partial correlation coefficient, and 21,37% contribution of emotional intelligence towards teacher performance, (3) There is a positive, but insignificant correlation between self-efficacy and teacher performance with 0,866 (ryx3) product moment coefficient correlation, 0,350 (ry.x3-x1,2,4) partial correlation coefficient, and 30,74% contribution of self-efficacy towards teacher performance, (4) There is a positive and significant correlation between organizational commitment and teacher performance with 0,551 (ryx4) product moment coefficient correlation, 0,286 (ry.x4-x1,2,3) partial correlation coefficient, and 7,98%, contribution of organizational commitment towards teacher performance, and (5) There is a positive and significant correlation of servant leadership, work climate, work motivation, job satisfaction and work discipline with Ry.1234 multiple correlation coefficient of 0,907 and there is a contribution of servant leadership, work climate, work motivation, job satisfaction and work discipline simultaneously by 82,2%